2020
DOI: 10.1021/jacs.0c07634
|View full text |Cite
|
Sign up to set email alerts
|

Modular and Stereoselective Synthesis of C-Aryl Glycosides via Catellani Reaction

Abstract: In this work, we describe a Catellani-type C−H glycosylation to provide rapid access to various highly decorated α-C-(hetero)aryl glycosides in a modular and stereoselective manner (>90 examples). The termination step is flexible, which is demonstrated by ipso-Heck reaction, hydrogenation, Suzuki coupling, and Sonogashira coupling. Application of this methodology has been showcased by preparing glycoside−pharmacophore conjugates and a dapagliflozin analogue. Notably, the technology developed herein represents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(38 citation statements)
references
References 78 publications
0
38
0
Order By: Relevance
“…[48] Very recently, the Cheng and Liang groups have independently achieved the C-H glycosylation reaction of aryl iodides by utilizing different glycosyl chlorides as the alkylation reagents. [49][50] Gratifyingly, azirines, epoxides and aziridines could also be used as alternative alkylating agents to promote the ortho alkylation of aryl halides (Schemes 18-20). In 2010, Lautens described an interesting Pd/NBE-catalyzed domino reaction to furnish indoles 34 by using 2H-azirines as bifunctional agents (Scheme 18).…”
Section: Scheme 15 Ortho-alkylation Of Heteroaryl Iodidesmentioning
confidence: 99%
See 1 more Smart Citation
“…[48] Very recently, the Cheng and Liang groups have independently achieved the C-H glycosylation reaction of aryl iodides by utilizing different glycosyl chlorides as the alkylation reagents. [49][50] Gratifyingly, azirines, epoxides and aziridines could also be used as alternative alkylating agents to promote the ortho alkylation of aryl halides (Schemes 18-20). In 2010, Lautens described an interesting Pd/NBE-catalyzed domino reaction to furnish indoles 34 by using 2H-azirines as bifunctional agents (Scheme 18).…”
Section: Scheme 15 Ortho-alkylation Of Heteroaryl Iodidesmentioning
confidence: 99%
“…[ 48 ] Very recently, the Cheng and Liang groups have independently achieved the C—H glycosylation reaction of aryl iodides by utilizing different glycosyl chlorides as the alkylation reagents. [ 49‐50 ]…”
Section: Typical Catellani Reactionsmentioning
confidence: 99%
“…3b). Third, glycosyl chloride was recently found to be a new type of alkyl electrophile for the Pd/NBE cooperative catalysis, but a superstoichiometric of structurally-modified NBE together with a phosphine ligand were found essential for catalytic activity 41 . Gratifyingly, the present Pd/L19 catalytic system was able to promote the ortho-glycosylative difunctionalization of iodoarenes in a highly efficient and selective manner without using any additional ligand, and the yields were even superior as compared with the previous method (Fig.…”
Section: Substrate Scopementioning
confidence: 99%
“…[51][52] In recent years, structurally modified norbornene (smNBEs) strategy provides a good solution to this problem. In 2015, the Dong group first reported the smNBE (C5-amidesubstitued), [53][54] Since that time, Yu 55 , Zhou, [56][57][58][59][60] Gu, 61 Ding, 62 Cheng, 63 Liang 64 and others developed a variety of the C2-, C5-and C6-substituted NBEs exhibited unique reactivity and higher selectivity compared to simple unsubstituted NBE. The amidesubstituted NBE was reported by Dong group [65][66][67][68] and estersubstituted NBE was reported by Yu group as the most effective two types of C2-substituted smNBEs greatly inhibits C-C reductive elimination of ANP to from by-product benzocyclobutanes, and effectively reduce the overall activation barrier.…”
Section: Introductionmentioning
confidence: 99%
“…In 2015, Dong et al first reported the smNBE (C5-amide-substituted), 53,54 and since then, Yu, 55 Zhou, 56–60 Gu, 61 Ding, 62 Cheng, 63 Liang 64 and others have developed numerous C2-, C5- and C6-substituted NBEs that exhibited unique reactivity and higher selectivity compared to the simple unsubstituted NBE. The amide-substituted NBE was reported by Dong et al 65–68 and the ester-substituted NBE reported by Yu et al was the most effective type of C2-substituted smNBEs that greatly inhibit the C–C reductive elimination of ANP to form the by-product benzocyclobutanes and effectively reduce the overall activation barrier.…”
Section: Introductionmentioning
confidence: 99%